Kajian Literatur: Dampak Sertifikasi Halal untuk Meningkatkan Daya Saing UMKM di Indonesia - Afina Fadhilah Hayya; Annisa Larasati; Hammas Az-Zakkiy; Seme, Bintang Putra; Jarot, Raja Haekal; Hananto, Djoko (Philosophiamundi, 2024)
This article explains how halal certification can have a positive impact on the competitiveness of MSMEs in Indonesia. The increasing trend and number of requests for halal products is an encouragement for the government and all related elements to continue to provide outreach and assistance to MSMEs to obtain halal certification through LPPOM-MUI and BPJPH. The results and discussion of this article contain explanations from several previously existing related literature regarding halal certification as well as the classification and competitiveness of MSMEs in Indonesia. The conclusion of this article is that socializing and assisting the halal certification process is important, because halal certificates and labels can support consumer confidence in a product and increase sales turnover. Keywords: halal certification, halal products, MSMEs Abstrak Artikel ini menjelaskan tentang bagaimana sertifikasi halal dapat memberikan dampak positif terhadap daya saing UMKM di Indonesia. Tren dan jumlah permintaan produk halal yang semakin meningkat merupakan dorongan pemerintah dan seluruh elemen terkait untuk terus melakukan sosialasi dan pendampingan UMKM guna mendapatkan sertifikasi halal melalui LPPOM-MUI dan BPJPH. Hasil dan pembahasan artikel ini memuat penjelasan dari beberapa literatur terkait yang telah ada sebelumnya mengenai sertifikasi halal serta klasifikasi dan daya saing UMKM di Indonesia. Kesimpulan dari artikel ini adalah sosialisasi dan pendampingan proses sertifikasi halal merupakan hal penting, sebab sertifkat dan label halal dapat menunjang kepercayaan konsumen terhadap suatu produk dan peningkatan omzet penjualan. Kata Kunci: sertifikasi halal, produk halal, UMKM